filter
Patent Information
- Application Number
- CN202580023419.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-01
- Filing Date
- 2025-02-19
- Publication Date
- 2026-10-30
AI Technical Summary
[0019]根据本公开,能够提供一种吸附性能优异的过滤器。
Smart Images

Figure FT_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This disclosure relates to filters on which a metal-organic framework material is loaded onto a substrate. Background Technology
[0002] Metal-organic frameworks (MOFs) are also known as porous coordination polymers. They are materials that form porous structures through coordination bonds between metal ions and organic ligands. They are expected to be used in applications that utilize gas adsorption / desorption properties or in catalysts, etc.
[0003] For example, Patent Document 1 describes the use of a moisture-absorbing plate with a metal-organic framework material attached to its surface as a component of a humidity control device.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Korean Patent Publication No. 10-2020-0140435 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] Patent Document 1 describes a method for manufacturing a moisture-absorbing board with a moisture-absorbing agent adhering to its surface by immersing the board in a solution containing a desiccant such as a metal-organic framework material, removing it, drying it, and then curing it by heat treatment as needed. However, the inventors have conducted research and found that such a moisture-absorbing board sometimes has insufficient adsorption performance (hereinafter also referred to as adsorption capacity) of adsorbed substances such as water.
[0009] Therefore, the purpose of this disclosure is to provide a filter that has a metal-organic framework material loaded on a substrate and has excellent adsorption performance.
[0010] means for solving problems
[0011] The present disclosure, which has accomplished the above-mentioned task, is as follows.
[0012] [1] A filter comprising a metal-organic framework material loaded on a substrate, wherein, The coefficient of variation of the amount (mol%) of the metal element M in the metal-organic framework material, as determined by fluorescence X-ray analysis, relative to the total amount of the target elements contained in the filter, is greater than 0% and less than or equal to 50%. The target element is an element other than O and C, and is an element with a peak intensity of 1 cps or more in fluorescence X-ray analysis.
[0013] [2] According to the filter described in [1], wherein the substrate does not contain the same metal element as the metal element M contained as the metal-organic framework material, or
[0014] The substrate contains the same metal element Lx as the metal element M that is included as the metal-organic framework material, and the content of metal element Lx in all metal elements contained in the substrate is less than 5 mol%.
[0015] [3] The filter according to [1] or [2], wherein the substrate contains a metal element L, the metal element L being at least one metal selected from the group consisting of Mg, Ca, Si, Fe, Na and Al. The metal element M of the metal-organic framework material is at least one selected from the group consisting of elements in the 4th to 6th periods and groups 3 to 12 of the long-period periodic table, Al, Ga, and In.
[0016] [4] The filter according to any one of [1] to [3], wherein the metal element M is Al.
[0017] [5] According to the filter described in [4], wherein the organic ligand constituting the metal-organic framework material is R(COO) - ) n (R is an n-valent group, where n is an integer greater than 2).
[0018] Invention Effects
[0019] According to this disclosure, a filter with excellent adsorption performance can be provided. Attached Figure Description
[0020] Figure 1 This is a schematic diagram showing the cross-sectional shape of the substrate used in the embodiments. Detailed Implementation
[0021] <Filter>
[0022] In the filter disclosed herein, a metal-organic framework material is loaded onto a substrate. The coefficient of variation of the amount (molar percentage) of the metal element M in the metal-organic framework material relative to the total amount of target elements contained in the filter is greater than 0% and less than or equal to 50%. The amount (molar percentage) of the metal element M relative to the total amount of target elements contained in the filter is determined by fluorescence X-ray analysis, and the coefficient of variation is calculated based on the measurement results of the amount of metal element M at multiple measurement points. The target elements are elements other than O and C, and are elements with a peak intensity of 1 cps or more in fluorescence X-ray analysis. The fluorescence X-ray analysis is performed using the apparatus and conditions described in the embodiments described later.
[0023] When the coefficient of variation of the amount (molar percentage) of metal element M in the metal-organic framework material is within the above-mentioned range, a filter with excellent adsorption performance for moisture and the like can be achieved. The coefficient of variation is preferably 40% or less, more preferably 35% or less, even more preferably 30% or less, and particularly preferably 20% or less. The coefficient of variation can be 10% or more. When there are multiple metal elements M, as long as the total amount meets the above-mentioned range of coefficients of variation, it is acceptable.
[0024] It should be noted that in this specification, "metal" also includes elements such as boron, silicon, germanium, arsenic, antimony, tellurium, selenium, polonium, and astatine, which are sometimes classified as half-metals.
[0025] When the composition of the loaded MOF is unknown, the filter can be cut at a cross-section where the substrate and the MOF loaded on the substrate can be observed, and the concentration distribution in the depth direction can be measured by SEM-EDX or similar methods, thereby identifying the metal element M of the MOF. In the filter of this disclosure, the MOF is loaded on the surface of the substrate; therefore, in the concentration distribution in the depth direction, the element with a concentration near the filter surface greater than that inside the substrate is the metal element of the MOF.
[0026] The MOF loading per unit area of the filter is, for example, 45 g / m². 2 The above, more preferably 60g / m 2 The maximum MOF loading per unit area of the filter can be 200 g / m². 2 the following.
[0027] According to the filter disclosed herein, the water absorption rate described in the embodiments described later can be adjusted to 9.5% or more. The water absorption rate is preferably 11.0% or more, more preferably 12.0% or more, even more preferably 13.0% or more, and can also be 20% or less.
[0028] Metal-Organic Framework Materials
[0029] MOFs are composed of metals and organic ligands. The metallic element M constituting the MOF can be, for example, at least one element selected from the group consisting of elements in periods 4 to 6 and groups 3 to 12 of the long-period periodic table, Al, Ga, and In. Preferably, it can be at least one element selected from the group consisting of Al, Ga, In, Ti, Zr, Hf, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, with Al being particularly preferred.
[0030] As an organic ligand, it is preferred to contain R(COO) selected from it. - ) n (R is an n-valent group, where n is an integer of 2 or more) represents at least one of the group consisting of carboxylate ions (carboxylate groups). R is preferably an aliphatic chain hydrocarbon group, an aliphatic cyclic hydrocarbon group, an aliphatic heterocyclic hydrocarbon group (a group in which one or more carbon atoms of an aliphatic cyclic hydrocarbon group are replaced by heteroatoms), an aromatic hydrocarbon group, an aromatic heterocyclic hydrocarbon group (a group in which one or more carbon atoms of an aromatic hydrocarbon group are replaced by heteroatoms), and most preferably an aromatic hydrocarbon group. The number of carbon atoms in R is preferably 2 to 30, more preferably 4 to 24, and even more preferably 6 to 18. n is preferably 2 or more and 4 or less, more preferably 2 or more and 3 or less, and most preferably 2.
[0031] The aforementioned aliphatic chain hydrocarbon group, aliphatic cyclic hydrocarbon group, aliphatic heterocyclic hydrocarbon group, aromatic hydrocarbon group, and aromatic heterocyclic hydrocarbon group may further include one or more functional groups X, wherein the functional group X is -OH and / or -NH2.
[0032] Aliphatic chain hydrocarbon groups can be straight-chain or branched, and can be saturated or unsaturated. Examples of aliphatic chain hydrocarbon groups include those obtained by removing n hydrogen atoms from ethane, ethylene, acetylene, butane, butene, or hexane.
[0033] Examples of aliphatic cyclic hydrocarbon groups include groups obtained by removing n hydrogen atoms from cyclopropane, cyclobutane, cyclohexane, cyclooctane, norbornene, or adamantane.
[0034] Examples of aliphatic heterocyclic hydrocarbon groups include groups obtained by removing n hydrogen atoms from pyrrolidine, piperidine, piperazine, or morpholine.
[0035] The preferred range of the number of carbon atoms in the aromatic hydrocarbon group is 6 or more and 30 or less, 6 or more and 24 or less, 6 or more and 18 or less, 6 or more and 12 or less, and 6 or more and 10 or less. Specifically, the aromatic hydrocarbon group is a group obtained by removing n (preferably 2 or 3) hydrogen atoms from benzene or biphenyl, especially a group obtained by removing n (preferably 2 or 3) hydrogen atoms from benzene.
[0036] The aromatic hydrocarbon group is preferably any one of the following formulas (A-1) to (A-9), more preferably any one of formulas (A-1) to (A-3), and even more preferably formula (A-2). In the following formulas (A-1) to (A-9), Indicates the bonding site.
[0037]
[0038] In the above formulas (A-1) to (A-9), at least one of the hydrogen atoms bonded to the carbon atom can be replaced by -OH and / or -NH2, and the hydrogen atoms bonded to the carbon atom may also be unsubstituted.
[0039] As aromatic heterocyclic hydrocarbon groups, examples include: pyrrole, pyrazole, imidazole, thiazole, etc. A group obtained by removing n hydrogen atoms from azole, pyridine, pyrimidine, pyridazine, pyrazine, or triazine.
[0040] The metal and organic ligand constituting the MOF can be appropriately combined within the aforementioned preferred range. For example, the preferred metal is at least one selected from the group consisting of Al, Ga, In, Ti, Zr, Hf, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, and the preferred organic ligand is R(COO) - ) n Wherein, R is an aromatic hydrocarbon group, n is a MOF of 2 or 3 carboxylate ions, more preferably Al metal, and the organic ligand is R(COO) - ) n , where R is any one of the above formulas (A-1) to (A-3), and n is a MOF of 2.
[0041] The molar ratio (expressed as metal ion / organic ligand) of metal ions (in various cases, their total amount) to organic ligands (in various cases, their total amount) is preferably 0.1 or more, more preferably 0.3 or more, further preferably 0.5 or more, particularly preferably 0.9 or more, and preferably 5 or less, more preferably 4 or less, further preferably 3 or less, and particularly preferably 2.5 or less.
[0042] The organic ligands constituting MOFs are the aforementioned R(COO-). n In the case of the carboxylate ion shown, relative to 1 mole of R(COO-) n The amount of metal constituting MOF is preferably 0.8 × n moles to 1.2 × n moles.
[0043] The BET specific surface area of MOF is, for example, 450 m². 2 / g~5000m 2 / g, preferably 450m 2 / g~800m2 / g, more preferably 500m 2 / g~750m 2 / g, further preferably 530m 2 / g~700m 2 / g, preferably 580m 2 / g~700m 2 / g.
[0044] MOFs can be manufactured using conventional methods, which involve reacting a metal compound containing metal ions constituting the MOF with an organic compound that serves as an organic ligand constituting the MOF in a solvent. More specifically, it is preferable to prepare a solution B obtained by completely dissolving the metal compound containing the metal ions and a solution A obtained by completely dissolving the organic compound that serves as the organic ligand, and to add either solution dropwise to the other to allow them to react.
[0045] The metal compound containing the metal ion constituting the MOF is preferably a sulfate, nitrate, acetate, chloride, bromide, or alkoxide of the metal, more preferably a sulfate. The organic compound that serves as the organic ligand constituting the MOF is preferably composed of R(COOH). n (R and n are the same as above) represent polycarboxylic acids.
[0046] The preferred solvents are water, alcohols such as methanol and ethanol, and amides such as N,N-dimethylformamide. Only one solvent may be used, or a mixture of two or more may be used. When reacting a metal compound containing the metal ions constituting the MOF with an organic compound that becomes the organic ligand constituting the MOF in the presence of water, the reaction is preferably carried out in the presence of a tertiary amine such as triethylamine.
[0047] After the reaction is complete (preferably after the dropwise addition is complete), the product is subjected to at least one of the following at a temperature of room temperature (e.g., 25°C) to 200°C for about 5 minutes to about 100 hours: reflux, stirring, and standing. The reaction product is then separated from the solvent by centrifugation or filtration, washed, and dried to obtain the target MOF.
[0048] <Substrate>
[0049] The substrate preferably contains a metallic element L, which is preferably at least one selected from the group consisting of Mg, Ca, Si, Fe, Na, and Al. More preferably, the substrate contains one or more oxides, Al (elemental Al), or Al alloys selected from the group consisting of Mg, Ca, Si, Fe, Na, and Al. Even more preferably, it contains one or more oxides selected from the group consisting of Mg, Ca, Si, Fe, Na, and Al. The total mass percentage of Mg, Ca, Si, Fe, Na, and Al contained in the substrate is preferably 95% by mass or more, more preferably 98% by mass or more, and even more preferably 99% by mass or more. Furthermore, relative to 100% by mass of the total mass percentage of each of the elements Mg, Ca, Si, Fe, Na, and Al contained in the substrate as oxides, the total mass percentage of Si oxides and Ca oxides is preferably 90% by mass or more, more preferably 95% by mass or more, and the upper limit can be 99.9% by mass. It should be noted that the composition of the substrate refers to the composition determined based on the results of SEM-EDX analysis of the substrate surface.
[0050] The substrate does not contain any metal element that is the same as the metal element M contained as the metal-organic framework material, or the substrate contains a metal element Lx that is the same as the metal element M contained as the metal-organic framework material. Of all the metal elements contained in the substrate, the content of metal element Lx is preferably 5 mol% or less, preferably 3 mol% or less, more preferably 2.5 mol% or less, and the lower limit is preferably 0%, but it can also be about 0.05 mol%. It should be noted that, similarly to the above, all metal elements contained in the substrate are those with an intensity ratio of 0.01% or more relative to the strongest intensity in fluorescence X-ray analysis. Furthermore, the identification and determination of the elements and their content in the substrate can also be performed, similarly to the above, by cutting the filter at a cross-section where the substrate and the MOF loaded on the substrate can be observed, and measuring the concentration distribution in the depth direction using SEM-EDX or the like, and specifying the substrate portion.
[0051] The substrate is preferably cylindrical with one or more through holes, and the shape of the column is preferably cylindrical, prismatic, or elliptical. The number of through holes is preferably two or more, and the shape of the holes in the cross-section perpendicular to the axial direction is preferably circular, triangular, quadrilateral, or hexagonal.
[0052] When the substrate is columnar with one or more through holes, the fluorescence X-ray analysis is preferably performed at a value measured on the substrate surface perpendicular to the axis of the through hole.
[0053] The cross-sectional area of the substrate section perpendicular to the axis of the through hole is preferably 300 mm². 2 ~40000mm 2More preferably 500mm 2 ~10000mm 2 The length of the substrate (axial length of the through hole) is preferably 10mm to 200mm, more preferably 20mm to 150mm.
[0054] Per 1cm of the substrate cross section perpendicular to the axis of the through hole 2 The preferred cell count (number of pores) per cm² is 10 pores / cm². 2 ~150 holes / cm 2 More preferably, 20 holes / cm 2 ~100 holes / cm 2 Further preferred is 30 holes / cm 2 ~80 holes / cm 2 .
[0055] The area (average value) of a single hole in a substrate cross-section perpendicular to the axis of the through hole is preferably 0.5 mm². 2 ~10mm 2 More preferably 1mm 2 ~8mm 2 More preferably 2mm 2 ~6mm 2 .
[0056] The thickness of the inner wall separating the pores is preferably 1 μm to 10000 μm, more preferably 10 μm to 5000 μm, and even more preferably 100 μm to 2000 μm. The thickness of the outer wall of the substrate is also preferably within the above range.
[0057] The total surface area of the inner and outer surfaces of the substrate, including the inner and outer walls, is preferably 0.01 m². 2 ~2m 2 More preferably 0.02m 2 ~1.8m 2 .
[0058] Preferably, it has a shape, cross-sectional area, and per 1cm of combining one or more of the above-mentioned substrates. 2 The substrate having preferred essential conditions such as the number of pores in the cross-sectional area, the area of one pore (average value), the thickness of the inner and outer walls, and the total area of the inner and outer surfaces including the inner and outer walls, and a water absorption rate of 9.5% or more, 11.0% or more, 12.0% or more, or 13.0% or more (upper limit, for example, less than 20%) as determined by the principles described in the embodiments described later.
[0059] <Filter Manufacturing Method>
[0060] The filter disclosed herein can be manufactured by immersing a substrate in a slurry containing MOF, lifting it out, and then drying it. Particularly important is the appropriate adjustment of the MOF concentration in the slurry and the number of coatings, as well as the MOF loading per unit area of the substrate. More specifically, it is preferable to perform any of the following operations: coating the substrate once with a slurry having a high MOF concentration (e.g., 20% to 40% by mass) and drying; coating the substrate with a slurry having a high MOF concentration (e.g., 20% to 40% by mass) and drying (first time); coating the substrate with a slurry having a lower MOF concentration than the first time (e.g., 10% or more by mass and less than 20% by mass) and drying (second time); or repeating the process of coating the substrate with a slurry having a low MOF concentration (e.g., 10% or more by mass and less than 20% by mass) and drying more than twice, such that the MOF concentration of subsequent slurries is not higher than that of the previous slurry. Furthermore, the preferred range for the MOF loading per unit area of the substrate is as described above. The MOF loading per unit area of the substrate can be adjusted by adjusting the time the substrate is immersed in the MOF-containing slurry, or by applying vibration to the substrate after it has been immersed in the MOF-containing slurry to adjust the amount of slurry.
[0061] In addition to MOF, the slurry preferably contains solvent, emulsifier, dispersant, and pH adjuster. Furthermore, the pH of the slurry is preferably 4 to 5.
[0062] The drying temperature and time of the substrate after impregnation with the MOF-containing slurry are, for example, 30°C to 600°C and 1 hour to 24 hours.
[0063] <Applications>
[0064] The filter disclosed herein is suitable for the adsorption and removal of gases and organic molecules, and can also be used as a component of a replaceable housing, humidification device, etc. Examples of gases include: water (water vapor), carbon dioxide, hydrogen, carbon monoxide, oxygen, nitrogen, hydrocarbons with 1 to 4 carbon atoms, noble gases, hydrogen sulfide, ammonia, sulfur oxides, nitrogen oxides, siloxanes, etc. Examples of organic molecules include: hydrocarbons with 5 to 8 carbon atoms, alcohols with 1 to 8 carbon atoms, aldehydes with 1 to 8 carbon atoms, carboxylic acids with 1 to 8 carbon atoms, ketones with 1 to 8 carbon atoms, amines with 1 to 8 carbon atoms, esters with 1 to 8 carbon atoms, amides with 1 to 8 carbon atoms, etc. It should be noted that the above-mentioned organic molecules may contain aromatic rings.
[0065] Example
[0066] The present disclosure is further illustrated below with examples. The present disclosure is not limited to the examples described below, and may be implemented with appropriate modifications that conform to the foregoing and hereinafter the spirit of the description, all of which are included within the technical scope of the present disclosure.
[0067] [Determination of BET surface area of MOF]
[0068] Since the adsorption area occupied by nitrogen molecules is known in advance, the amount of gas molecules adsorbed only on the sample surface is measured, and the surface area of the MOF sample is determined according to the BET adsorption isotherm.
[0069] Sample preparation: In order to remove water from the sample, it was heated overnight under reduced pressure at 200°C and below 10 Pa.
[0070] Device: BELSORP-mini manufactured by MicrotracBEL Co., Ltd.
[0071] Preprocessing conditions: (ai) Place a volume-reducing glass rod (for standard sample tubes) in a standard sample tube and seal it using a quick seal. Prepare the sample to be measured for this set of sample tubes (maximum of 3 samples per measurement), connect it to the pretreatment device (BELPREP VACII), purge the air from the sample tubes, and then introduce N2 gas (purity ≥ 99.999%) to atmospheric pressure.
[0072] (a-ii) Then, the sample tube is removed from the pretreatment machine and its weight is measured three times using a precision balance (displaying at least four decimal places) to obtain its average value (W1). An ion generator is used to eliminate the influence of static electricity when using the precision balance.
[0073] (a-iii) Measure about 50 mg of the sample to be measured on weighing paper and place the sample directly into the spherical part at the bottom of the standard sample tube using a long-necked funnel.
[0074] (a-iv) Return the glass rod to the sample tube, seal it with a quick seal, and then measure the overall weight once to temporarily confirm the amount of sample added.
[0075] (av) Connect the sample tube containing the sample to the pretreatment device and vent the air from the sample tube.
[0076] (a-vi) After the pressure inside the sample tube is sufficiently low, heating begins (with continued evacuation).
[0077] Measurement conditions: (bi) After the pretreatment (vacuum heating) is completed, the sample tube is kept under reduced pressure to dissipate heat. After reaching room temperature, N2 gas is introduced to atmospheric pressure and removed from the device.
[0078] (b-ii) The weight of the sample tube containing the pretreated sample was measured three times using a precision balance, and the average value (W2) was obtained. W2-W1 was calculated to obtain the weight of the sample.
[0079] (b-iii) Input the sample weight, N2 gas information at liquid nitrogen temperature (second virial coefficient, etc.) into the measurement software, input the relative pressure to be measured, and press the measurement start button.
[0080] Then, following the software instructions, set up the Dewar flask filled with liquid nitrogen and the sample tube, and then perform the measurement.
[0081] MOF loading (g / m³) 2 [Determination of]
[0082] The weight of the filter substrate before and after MOF loading was measured separately. The weight difference was then calculated based on the surface area (m²) of the substrate. 2 ) Calculate the MOF load per unit area of the filter.
[0083] [Determination of coefficient of variation]
[0084] X-ray fluorescence (XRF) analysis was performed on the surface of the filters fabricated in the examples and comparative examples. Elements other than O and C with a peak intensity of 1 cps or higher in the XRF analysis were considered as all elements contained in the filter. It should be noted that the target elements in the following examples and comparative examples are Mg, Ca, Si, Fe, S, Na, and Al. The ratio (molecular percentage) of the metal element M (Al in the following examples) contained in the MOF relative to all elements contained in the filter was determined at each measurement point, and the coefficient of variation of the concentration of metal element M contained in the MOF was calculated based on the following formula.
[0085] Coefficient of variation RSD (%) = 100 × Standard deviation of metal element M concentration B / Average concentration of metal element M A
[0086] The XRF analysis conditions are as follows, and the elemental ratios are calculated using the software accompanying the device described below.
[0087] Device: XGT-7200VNM manufactured by Horiba Manufacturing Co., Ltd.
[0088] X-ray irradiation diameter: 1.2mm
[0089] Tube voltage: 50kV
[0090] Tube current: Automatic mode (automatically adjusts to achieve optimal DT% (dead time))
[0091] Measurement mode: point analysis
[0092] Measurement time: 10 seconds / point
[0093] Measurement points: 480 points in total, measuring 24×20 mm at 1.25 mm intervals.
[0094] Environment: Vacuum environment
[0095] [Determination of water absorption]
[0096] The weights of the MOF-loaded filters and the substrates before MOF loading were measured in both the examples and comparative examples, and the amount of MOF loaded on the filters, W, was calculated. MOF .
[0097] In addition, the filters prepared in the examples and comparative examples were pretreated by being kept at 100°C for 2 hours in an atmospheric atmosphere, and then the weight W1 was measured. Then, the filters were allowed to cool naturally at 25°C and 50% relative humidity, and then left to stand at 25°C and 50% relative humidity for 12 hours, and the weight W2 was measured.
[0098] Then, the water absorption rate of the filter is calculated using the following formula.
[0099] Water absorption rate (%) = 100 × (W2 - W1) / W MOF
[0100] (Preparation Example 1-1: Preparation of Metal-Organic Framework Material 1)
[0101] In a 13L autoclave, 3.91 mol of isophthalic acid and 3200 mL of DMF (N,N-dimethylformamide) were mixed at 25°C until completely dissolved to obtain solution A. Separately, solution B was prepared by mixing 3.75 mol of Al2(SO4)3·nH2O (n=14–18) and 4800 mL of deionized water until completely dissolved. Solution B was added dropwise to solution A over 45 minutes at 25°C. The resulting mixture was then refluxed at 135°C for 12 hours to obtain a suspension. This suspension was pressure filtered, and the precipitated solids were washed three times with 1500 mL of DMF and three times with 1500 mL of methanol. The resulting filter cake was dried in a vacuum drying oven at 50°C for 3 hours to obtain 865.23 g of the product (MOF1) (yield 94%).
[0102] (Preparation Examples 1-2: Preparation of Metal-Organic Framework Material 2)
[0103] Solution A was prepared in a 13L autoclave by dissolving 3.50 mol of isophthalic acid and 9.94 mol of triethylamine in 8060 mL of water. Solution B was prepared by mixing 2.54 mol of Al2(SO4)3·nH2O (n=14~18) with 540 mL of deion-exchanged water and dissolving it completely. Solution B was added dropwise to solution A at 25°C over 45 minutes. Then, the mixture was refluxed at 100°C for 12 hours to obtain a suspension. The suspension was then pressure filtered, and the precipitated solids were washed twice with 2000 mL of deion-exchanged water and twice with 2000 mL of methanol. The resulting filter cake was dried in a vacuum drying oven at 100°C for 6 hours to obtain 721.97 g of the product (MOF2) (yield 97.9%).
[0104] (Preparation Example 2: Preparation of a slurry containing a metal-organic framework material)
[0105] The metal-organic framework material obtained in Preparation Example 1-1 or Preparation Example 1-2 was mixed with a solvent to prepare a slurry containing the metal-organic framework material with a pH of 4 to 5.
[0106] Example 1
[0107] A 30mm × 25mm × 50mm long substrate containing wollastonite was immersed in a slurry prepared by mixing metal-organic framework materials in an amount of concentration as described in Table 1 below, according to the method of Preparation Example 2. The substrate was then lifted out and dried (first time). The same operation was performed for a second, third, and fourth immersion and drying, except that the concentration of metal-organic framework materials in the slurry was changed to the concentration described in Table 1, thereby producing a filter with metal-organic framework materials loaded on the substrate.
[0108] The above-mentioned substrate is made of having Figure 1 The structure shown consists of a corrugated core 1, a face paper 2, and a back paper 3 bonded to the core 1, with a corrugation height h of approximately 1.7 mm and a corrugation width p (pitch) of approximately 2.7 mm, forming a stacked structure of 17 layers. Furthermore, fluorescence X-ray analysis of only the substrate revealed the presence of Mg, Ca, Si, Fe, Na, and Al. Of all the metal elements contained in the substrate, Al accounted for 2.1 mol%.
[0109] Examples 2-3, Comparative Example 1
[0110] The substrate of the dimensions listed in Table 1 was immersed in the slurry and dried using the slurry concentration and number of times specified in Table 1. Otherwise, the operation was the same as in Example 1, thereby producing a filter with a metal-organic framework material loaded on the substrate.
[0111] The results are shown in Table 1.
[0112] [Table 1]
[0113] Label Explanation
[0114] 1...core
[0115] 2... tissues
[0116] 3...lining paper
[0117] h……corrugated height of the core
[0118] p... the corrugated width (spacing) of the core.
Claims
1. A filter comprising a metal-organic framework material loaded on a substrate, wherein, The coefficient of variation of the amount (mol%) of the metal element M in the metal-organic framework material, as determined by fluorescence X-ray analysis, relative to the total amount of the target elements contained in the filter, is greater than 0% and less than or equal to 50%. The target element is an element other than O and C, and is an element with a peak intensity of 1 cps or more in fluorescence X-ray analysis.
2. The filter according to claim 1, wherein, The substrate does not contain the same metal element as the metal element M included as the metal-organic framework material, or The substrate contains the same metal element Lx as the metal element M included as the metal-organic framework material, and the content of metal element Lx in all metal elements contained in the substrate is less than 5 mol%.
3. The filter according to claim 1 or 2, wherein, The substrate contains a metallic element L, which is at least one metal selected from the group consisting of Mg, Ca, Si, Fe, Na, and Al. The metal element M of the metal-organic framework material is at least one selected from the group consisting of elements in the 4th to 6th periods and groups 3 to 12 of the long-period periodic table, Al, Ga, and In.
4. The filter according to claim 1 or 2, wherein, The metallic element M is Al.
5. The filter according to claim 4, wherein, The organic ligand constituting the metal-organic framework material is R(COO) - ) n (R is an n-valent group, where n is an integer greater than 2).
Citation Information
Patent Citations
Dehumidifying apparatus and method using thermoelectric module
KR1020200140435A
